Penerapan metode rating scale dengan pendekatan Analytical Hierarchy Process (AHP) pada penilaian kinerja karyawan PT. Omega Mas - Aryaseta, Aziz Wisnu; Hadidjija, Kusno; Utomo, Eko Budi; Putra, Muhammad Hengki Riawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study evaluates the employee performance of PT. Omega Mas using the AHP method and rating scale. Conducted from December 2023 to February 2024, it involved 133 employees from 14 departments. The criteria included maturity, work attitude, teamwork, discipline, and work results. The results showed that "work results" had the highest weight (0.51), with "quantitative work" as the primary sub-criterion. From the performance assessment, 6 employees were categorized as "very good," 47 as "good," and 80 as "sufficient." The conclusion is that this evaluation helps the company improve its human resources quality and competitiveness in the market.